Cost effective management of early blight disease of potato (Solanum tuberosum) caused by Alternaria solani - SHARMA, SHAILBALA; KUMAR, AMARENDRA; KUMAR, SANJEEV; KUMAR, RAKESH (The Indian Journal of Agricultural Sciences, 2022)
Early blight disease of potato (Solanum tuberosum L.) caused by Alternaria solani (Ellis and Martin), is one of the most important fungal disease throughout the potato growing areas. Field experiments were conducted during winter (rabi) season, 2018–19 and 2019–20 at Vegetable Research Centre, Govind Ballabh Pant University of Agriculture and Technology, Pantnagar, Uttarakhand for evaluating fungicides against early blight of potato. All the fungicides (mancozeb, hexaconazole, difenoconazole and chlorothalonil) were evaluated in vitro using poison food technique as well as field conditions. In vitro study revealed that chlorothalonil 75% wp gave the best results and showed 18.0 mm, 17.67 mm, 16.33 mm, 12.33 mm and 8.33 mm mycelial growth of Alternaria solani @25 ppm, 50 ppm, 100 ppm, 150 ppm and 200 ppm concentration at 7 days after inoculation. In field condition, chlorothalonil 75% WP @0.2% applied as foliar sprays at 10 days interval resulted the lowest disease severity i.e. 22.50% with highest tuber yield (317.90 q/ha). The findings regarding the economics of the potato cultivation clearly revealed that the treatment chlorothalonil @0.2% gave the highest benefit cost ratio i.e. 2.96. The early blight disease of potato may be controlled by applying chlorothalonil at a concentration of 0.25 three times at a 10-day interval, which increased production and provided extra benefits to farmers.